Analisis Pengaruh Harga dan Kualitas Produk terhadap Permintaan Produk Kerupuk Opak UD. KARYA BERSAMA - Yuliana Simbolon; Dariz Radyananda Barus; Sasti Permata; Aurora Elise Putriku (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of price and product quality variables on the demand for Kerupuk Opak at UD. Karya Bersama. This research is a quantitative study utilizing primary data collected through questionnaires distributed to 30 customers, using a saturated sampling technique. Data collection methods include questionnaires and literature studies. Instrument testing consists of validity and reliability tests, while classical assumption tests include normality, heteroscedasticity, and multicollinearity tests. Data were analyzed using multiple linear regression with the help of SPSS version 26. The results show that the price variable does not have a significant effect on product demand (tvalue = -0.253 < ttable = 1.70329; significance > 0.05), whereas the product quality variable has a significant effect on product demand (tvalue = 5.391 > ttable = 1.70329; significance < 0.05). Simultaneously, price and product quality significantly influence product demand (Fvalue = 65.853 > Ftable = 3.35; significance = 0.000 < 0.05).